MICROBIOLOGICAL AND PHYSICOCHEMICAL QUALITY OF HOSPITAL “X” EFFLUENT IN ABA, ABIA STATE, NIGERIA. - C. C, Ike,; D. K., Akwari, (IJRDO-Journal of Applied Science, 2017)
The microbiological and physicochemical quality of hospital “x” effluent was assessed. The studywas done using standard microbiological and physicochemical methods. Bioloads had highestcounts in the late hour (LH) samples than in the early hour (EH) samples: total heterotrophicbacteria (CFU/ml) - 7.9 x 104 ± 0.15 (LH), 6.7 x 104± 0.20 (EH), total coliform (CFU/ml) - 2.2 x10³ ± 0.09 (LH), 1.8 x 10³ ± 0.04 (EH), and fungi (CFU/ml) - 3.5 x 10³ ± 0.05 (LH), 3.1 x 10³ ±0.17 (EH), The recorded bioload results were higher than regulatory standards as stipulated byNational Environmental Standards and Regulatory Enforcement Agency (NESREA). Most of thephysicochemical values were high in the LH samples than in EH samples, and all the values areabove regulatory standards (NESREA) except for temperature and nitrate that had values belowstandards. Total phosphorus had values slightly above regulatory standards (NESREA). A total offour bacterial species (Escherichia coli, Salmonella, Staphylococcus and Enterobacter species)and four fungal species (Aspergillus, Candida, Cryptococcus and Penicillium species) wereisolated respectively. Escherichia coli had the highest prevalence for bacteria (33.3%), whileAspergillus species had the highest prevalence for fungi (42.9%). This study has shown thathospital wastewater/ effluent is highly polluted, contaminated, infectious and if discharged intothe environment untreated, it can pose serious health hazards to humans. Therefore, there is needfor strict regulations concerning treatments and monitoring by regulatory bodies on the affectedestablishments to avert epidemics.